PENGARUH CURRENT RATIO DAN RETURN ON EQUITY TERHADAP PRICE EARNING RATIO PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSAEFEK INDONESIA (BEI) PERIODE 2013-2017 - Hade Chandra Batubara; Diana Dwi Astuti; Ramadani Ramadani (Universitas Serambi Mekkah, 2019)
This study aims to determine whether there is a relationship between Current Ratio and Return On Equity both partially and simultaneously to Price Earning Ratio. The research approach uses an associative approach. The population that is the object of this research is the Food and Beverage Company listed on the Indonesia Stock Exchange, which is as many as eighteen companies, but the sample taken is seven companies. The sampling criteria use Purposive Sampling techniques. The technique of collecting data uses documentation studies. Regression requirements test using normality test, heteroscedasticity test, multicollinearity test and autocoleration test. The data analysis technique uses multiple linear regression, hypothesis testing (t test and F test) and coefficient of determination. Processing data in this study using SPSS Software (Statistical Product and Service Solution) 16 For Windows. The results of the study prove that the Current Ratio partially has a negative effect but not significantly to Price Earning Ratio and Return On Equity which have a negative effect but not significantly to Price Earning Ratio.